TLR4 signaling is essential for survival in acute lung injury induced by virulent Pseudomonas aeruginosa secreting type III secretory toxins - Faure, Karine (BioMed Central, 2004)
BACKGROUND: The relative contributions of the cytotoxic phenotype of P. aeruginosa expressing type III secretory toxins and an immunocompromised condition lacking normal Toll-like receptor 4 (TLR4) signaling in the pathogenesis of acute lung injury and sepsis were evaluated in a mouse model for Pseudomonas aeruginosa pneumonia. By using lipopolysaccharide-resistant C3H/HeJ mice missing normal TLR4 signaling due to a mutation on the tlr4 gene, we evaluated how TLR4 signaling modulates the pneumonia caused by cytotoxic P. aeruginosa expressing type III secretory toxins. METHODS: We infected C3H/HeJ or C3H/FeJ mice with three different doses of either a cytotoxic P. aeruginosa strain (wild type PA103) or its non-cytotoxic isogenic mutant missing the type III secretory toxins (PA103ΔUT). Survival of the infected mice was evaluated, and the severity of acute lung injury quantified by measuring alveolar epithelial permeability as an index of acute epithelial injury and the water to dry weight ratios of lung homogenates as an index of lung edema. Bacteriological analysis and cytokine assays were performed in the infected mice. RESULTS: Development of acute lung injury and sepsis was observed in all mouse strains when the cytotoxic P. aeruginosa strain but not the non-cytotoxic strain was instilled in the airspaces of the mice. Only C3H/HeJ mice had severe bacteremia and high mortality when a low dose of the cytotoxic P. aeruginosa strain was instilled in their lungs. CONCLUSION: The cytotoxic phenotype of P. aeruginosa is the critical factor causing acute lung injury and sepsis in infected hosts. When the P. aeruginosa is a cytotoxic strain, the TLR4 signaling system is essential to clear the batcteria to prevent lethal lung injury and bacteremia.